USERSâ RESPONSES OF THE AUTHENTIC ASSESSMENT INSTRUMENT DEVELOPED TO ASSESS PROBLEM-SOLVING SKILLS OF PROSPECTIVE BIOLOGY TEACHERS IN FIELD PRACTICE ACTIVITIES - IBRAHIM, YUSUF; CARTONO, CARTONO; TRESNAWATI, CITA; NURDIANI, NIA (Sriwijaya University Learning and Education International Conference, 2016)
This study is the final stage of study designed by using the method of Educational Research and Development (R & D) to generate a tested authentic assessment instrument model so thatit can be used to assess problem-solving skills of prospective biology teachers in field practice activities. The assessment instruments, that have been developed and tested on limited audiences in the earlier study stage, have very high validity and reliability for measuring learning outcomes in the cognitive domains (0.877 and 0.949), have high validity and reliability in assessing observing skills (0.776 and 0.866), communication skills (0.665 and 0.581), developing proposals (0.854 and 0.884) and collecting specimens (0.676 and 0.400), but only until sufficient and medium categories for the skill measurement of taking notes of process (0.607 and 0.153), and making report of the result of field practice (0.607 and 0.153). The instruments also have sufficient validity (0.589) and high reliability (0.75) for the measurement of scientific attitude. At the final stage of this study, the instrument was then used by the 10 supervisors to assess the field practice activities involving 120 students of prospective biology teachers from a private university in Bandung, Indonesia. Each supervisor assessed footages of 5 students. The result of the study shows that the supervisors who are the assessment instrument users give good responses evenly (X = 3,58 Â± 0,12) on questions with following indicators: The result shows that the supervisors who are the assessment instrument users give good responses evenly (x = 3.58 Â± 0.12) to questions with following indicators: the suitability of the instruments with the needs in the field, the suitability of the instruments with their columns, instrument effectiveness in the assessment, as well as ease of use of the instrument. The participating students of field practice who are assessed state that in-advance explanation about techniques and aspects of the assessment before the implementation of the field practice can encourage them to conduct the field practice much better, in order to obtain higher learning outcomes.Making improvements and conducting further tests on the authentic assessment instrument developed in this study are suggested so that the instrument can become a measuring tool of learning outcome which has higher reliability and validity.